2016
DOI: 10.1177/0021998316682363
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of graphene–carbon nanotube-reinforced metal matrix composites: A molecular dynamics study

Abstract: Single layer graphene sheets and carbon nanotubes have resulted in the development of new materials for a variety of applications. Though there are a large number of experimental and numerical studies related to these nanofillers, still there is a lack of understanding of the effect of geometrical characteristics of these nanofillers on their mechanical properties. In this study, molecular dynamics simulation has been used to assess this issue. Two different computational models, single layer graphene sheets–c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 53 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Eqs. (1)-(3) can be written in the generalized form of Hamiltonian pertaining to silver atoms as given by equation (4) beloŵ̂̂∑…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eqs. (1)-(3) can be written in the generalized form of Hamiltonian pertaining to silver atoms as given by equation (4) beloŵ̂̂∑…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Solidification and organization of metallic materials in the confined region has been found to direct impact many desirable properties of metal matrix nano-composite, including mechanical [1,2], thermal [3][4][5], electrical [6][7][8], optical [9][10], anti-microbial [11][12][13], etc. The accountable factors which direct the above properties are the interactions and wettability of metal atoms with interface, stress transfer, the mobility of thermal vibrations, electronic conductions and chemical reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The plate-like structure of GSs has improved mechanical interlocking with matrix material because of the enlarged interfacial area between GS and matrix, which subsequently results in improved stiffness and strength of the nanocomposite materials than CNT nanocomposites. [11][12][13] Sharma et al 14 have made a comparative molecular dynamics (MD)-based study between CNT and GS-reinforced copper nanocomposite in terms of elastic properties. It was reported in the study that, for an 8% volume fraction of reinforcement, the elastic modulus of CNT nanocomposite is enhanced by 13%, whereas for the same volume of GS reinforcement, the enhancement in elastic modulus is reached up to 18%.…”
Section: -10mentioning
confidence: 99%
“…Graphene is an ideal reinforcement agent for highperformance composites due to its superb mechanical and physicochemical properties [1][2][3][4][5][6]. Recently, polymer-and metal-based composites [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] reinforced by graphene have gained tremendous attention from the scientific community. Compared with polymer-based composites, composites with metal matrix can provide higher stiffness and strength and service under a higher temperature, which makes them have the potential for more critical applications in industry, especially in the aerospace and automobile industry.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with polymer-based composites, composites with metal matrix can provide higher stiffness and strength and service under a higher temperature, which makes them have the potential for more critical applications in industry, especially in the aerospace and automobile industry. Several researchers have reported in recent years [9][10][11][12][13][14][15][16][17][18][19][20][21] on experimental and numerical studies of graphene-reinforced metal composites. The numerical studies [16][17][18][19][20][21] mainly based on the method of molecular dynamics (MD) simulations indicated that the material properties of metal composites can be significantly improved by applying single-layer graphene reinforcement.…”
Section: Introductionmentioning
confidence: 99%